Penguatan Kualitas Pelayanan Publik melalui Standar Pelayanan Prima dan Indikator Kinerja Terukur - Sri Yuliyanti Mozin; Alisa Tutulango; Siti Vahizrah Carlos; Faja Diasti Paputungan; Fathiya H (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Public service quality has emerged as a crucial metric for assessing how well the government functions and the efficiency of its administration. Recently, rising expectations from the public have led gov-ernments to offer services that are open, responsible, effective, and attuned to citizens' needs. Alongside administrative changes and the evolution of governance models focused on efficiency and citizen satisfaction, the appetite for high-quality public services has surged. Nonetheless, numerous public entities continue to struggle with providing reliable and top-notch services due to a lack of defined service norms and systems for measuring performance. The purpose of this research is to investigate ways to enhance public service quality by establishing robust service standards and quantifiable performance metrics. The study employs a qualitative descriptive methodology, drawing on a review of relevant lit-erature from the past seven years. Multiple academic sources were analyzed to uncover essential ideas, frameworks, and empirical evidence concerning public service management, the enhancement of service quality, and the assessment of performance in governmental organizations. The results show that adopting well-defined service standards, along with measurable performance metrics, can greatly en-hance service effectiveness, accountability, and overall public satisfaction. Additionally, merging prin-ciples of service excellence with quantifiable indicators promotes transparency, boosts organizational performance, and fosters ongoing improvements in service delivery. The research concludes that to enhance public service quality, a structured framework for service standards, ongoing performance assessments, and a firm organizational dedication to innovation and service enhancement are necessary.